Connections of the Superior Paraolivary Nucleus of the Rat: II. Reciprocal Connections with the Tectal Longitudinal Column - Viñuela, Antonio; Aparicio, M.-Auxiliadora; Berrebi, Albert S.; Saldaña, Enrique (Frontiers in Neuroanatomy, 2011)
The superior paraolivary nucleus (SPON), a prominent GABAergic center of the mammalian auditory brainstem, projects to the ipsilateral inferior colliculus (IC) and sends axons through the commissure of the IC (CoIC). Herein we demonstrate that the SPON is reciprocally connected with the recently discovered tectal longitudinal column (TLC). The TLC is a long and narrow structure that spans nearly the entire midbrain tectum longitudinally, immediately above the periaqueductal gray matter (PAG) and very close to the midline. Unilateral injections of biotinylated dextran into the SPON of the rat label abundant terminal fibers in the TLC of both sides, with an ipsilateral predominance. The SPON provides a dense innervation of the entire rostrocaudal extent of the ipsilateral TLC, and a relatively sparser innervation of the caudal and rostral portions of the contralateral TLC. SPON fibers reach the TLC by two routes: as collaterals of axons of the CoIC, and as axons that circumvent the ipsilateral IC before traveling in the deep layers of the superior colliculus. The density of these projections identifies SPON as a significant source of input to the TLC. Other targets of the SPON discovered in this study include the deep layers of the superior colliculus and the PAG. The same experiments reveal numerous labeled cell bodies in the TLC, interspersed among the labeled SPON fibers. This observation suggests that the SPON is a significant target of TLC projections. The discovery of novel reciprocal connections between the SPON and the TLC opens unexpected avenues for investigation of sound processing in mammalian brainstem circuits.